GENERAL DESCRIPTION OF THE INSTITUTE OF JURISDICTION AND METHODOLOGICAL ISSUES OF ITS LEGAL REGULATION IN THE RA NEW CRIMINAL PROCEDURE CODE - Marabyan, Sergey (State and Law, 2021)
This article is devoted to the discussion of the Institute of Jurisdiction and methodological issues of its legal regulation in the RA new Criminal Procedure Code. The author finds that Jurisdiction, being one of the Criteria determining a Court established by law, is not properly regulated by the RA new Criminal Procedure Code. Both the current code and the new code do not define the definition of Jurisdiction, moreover, it is impossible to trace the meaning that the Legislature gave to it from the legal regulations on its various aspects. In order to determine the Jurisdiction of a criminal case, in one case, the court area of ​​the place of commission of the crime or the seat of the body of the pre-trial investigation or the place of residence or registration of the defendant is taken as a basis; in the case of a legal person - the characteristics of the place of commission of the crime, the location of the legal person or the place of reaching dangerous consequences (if the crime was committed outside the territory of the Republic of Armenia or the place of the commission could not be determined); and in the other case, the basis are the cases heard by the courts of first instance, appellation and cassation. Moreover, from the substantive analysis of the definitions "Jurisdiction of General Courts of First Instance", "Jurisdiction of the Criminal Court of Appeal", "Jurisdiction of the Criminal Chamber of the Court of Cassation" given in the new Code, "Competence of the General Court of first Instance", "Specialization of Judges in the General Court of first Instance", "Competence of the Court of Appeal" and "Competence of the Court of Cassation" given in the RA "Judicial Code of the Republic of Armenia" Constitutional Law, becomes clear, that the legislature has essentially co-ordinated them (Competence and Jurisdiction of the court), which in our opinion is methodologically problematic, as they, being independent legal definitions, called to solve various legal problems, should not be co-ordinated. Based on the above, the author discussed the issues of the general description of the definitions of Competence and Jurisdiction of the Court, their interconnectedness, delimitation and has offered precise suggestions on the legal regulation of different aspects of the Institute of Jurisdiction in the new Criminal Procedure Code of the Republic of Armenia.